Influência do número de hastes e do espaçamento no crescimento e produção de fisális - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Recent insight into the category of small fruits the interest in aroused interest to its neutraceutical characteristics. Please take it to a growing growth bush, make it necessary, such as training and pruning for the growth of the aerial part of the plant with the soil, and balance the source drain ratios. Another important point is the space between the rows of plants used, which can increase and produce the use of the area. The work was to evaluate the influence of the number of weighed and organized between the rows without growth and the production of fish cultivated in a subtropical environment in the West Frontier region of Rio Grande do Sul. The experimental design was used as a block of data with more than four blocks in which they were contained as subplots. The main plots consisted of spaces of 1.5 and 3 meters between rows and subplots of a training field with 4, 6 and 8 steps per plant and semantic evaluation, with a trimatorial arrangement (spacing x number of accesses x evaluations ). Each plot was constituted of five plants, being evaluated as three plants. There was triple interaction for number of leaves and main path height. The highest height of the main stem was found in plants with 4 stems for growth of 1.5 meters and in plants with 8 stems for spacing of 3 meters and for 4 stems as larger plants were cultivated in spacing of 1.5 meters. The number of leaves per plant can only be 8 times greater than the number of times the amount of filming was greater than 3 m between rows, for the two spacings the largest number of leaves was found in 8-stem plants. The diameter of stems longer than the behavior being that plants with 4 stems should have the largest diameters. For the most productive versions, the greatest highlight is significant, with fruit mass with capsule, fruit mass and number of fruits being greater in spacing of 1.5 meters. The average fruit consumption varies between five harvests being higher in the fourth harvest.
Keywords: Physalis peruviana; População; Ppoda; Population; Pruning; CNPQ::CIENCIAS AGRARIAS